A man with Erb's disease. Issue 6 (27th May 2022) - Leddy, Sara; Jaffer, Fatima; Lipnicka-Khan, Monika; Nigel Leigh, P
Abstract : A man, currently aged 72, developed a spastic paraparesis without sensory abnormalities progressing to wheel-chair dependence and late urinary incontinence over 14 years. Apart from a history of type 2 diabetes mellitus, he was otherwise well. Extensive blood and CSF investigations including screening for HIV, HTLV1, syphilis, and Lyme disease were normal or negative. There was no evidence of neuropathy or denervation on EMG. MRI showed mild non-specific white matter signal change in both cerebral hemi- spheres. A provisional diagnosis of primary lateral sclerosis (PLS) was revised with the finding of elevated Very Long Chain Fatty Acids (VLCFAs). Genetic testing revealed a novel missense variant c.1771C>G p. (Arg591Gly) in exon 7 of the ABCD1 gene. Mutation in ABCD1 transporter leads to accumulation of VLCFAs in the peroxisomes and cytosol which is toxic, causing oxidative stress and demyelination in the CNS and PNS. Literature review did not reveal reports of AMN mimicking PLS. Our patient highlights the importance of screening VLCFAs (abnormal in 99% of men with AMN) in suspected PLS, a diagnosis of exclusion. Diagnosis of ALD/AMN allows genetic counselling, screening for adrenal failure, and access to stem cell therapy for children with asymptomatic cerebral onset ALD. sara.leddy1@nhs.net